Ethopedagogical Aspects of Education and Formation of Harmoniously and Comprehensively Developed Personality in the Territorially Neighboring Communities (Mahalla). - U.V.Mamadjanov; U.K.Khudaynazarov.; H.I.Islamov. (Zien Journals, 2022)
The scientific article discusses some issues of formation and education comprehensively personalities and the role of ethno-pedagogy and territorial-neighboring communities (Mahalla) in this pedagogical process.
Keywords: Mahalla; territorial-neighboring; community; ethnopedology